2015
DOI: 10.1111/myc.12426
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Histoplasma capsulatum using rolling circle amplification

Abstract: Histoplasmosis is a systemic fungal disease that occurs worldwide, causing symptomatic infection mostly in immunocompromised hosts. Etiological agent is the dimorphic fungus, Histoplasma capsulatum, which occurs in soil contaminated with bird or bat droppings. Major limitation in recognition of H. capsulatum infections is the low awareness, since other diseases may have similar symptomatology. The molecular methods have gained importance because of unambiguous diagnostic ability and efficiency. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…When two complementary ends of a probe match the template, they are juxtaposed and ligated by T4 ligase, then, RCA primers anneal and amplification occurs [83]. Applied to DNA isolated from pure cultures, RCA-padlock probes not only successfully differentiated among a wide range of medically important fungal species but also distinguished various genotypes of Cryptococcus and Trichophyton species [84][85][86][87][88][89][90][91][92][93][94][95]. However, although RCA is extensively applied to analyze DNA samples derived from pure cultures, only a few studies employed this technique for direct detection of pathogens in clinical samples and their results indicated poor sensitivity [84].…”
Section: Rcamentioning
confidence: 99%
“…When two complementary ends of a probe match the template, they are juxtaposed and ligated by T4 ligase, then, RCA primers anneal and amplification occurs [83]. Applied to DNA isolated from pure cultures, RCA-padlock probes not only successfully differentiated among a wide range of medically important fungal species but also distinguished various genotypes of Cryptococcus and Trichophyton species [84][85][86][87][88][89][90][91][92][93][94][95]. However, although RCA is extensively applied to analyze DNA samples derived from pure cultures, only a few studies employed this technique for direct detection of pathogens in clinical samples and their results indicated poor sensitivity [84].…”
Section: Rcamentioning
confidence: 99%
“…Besides, some studies have already distinguished several CBM agents of the genus F. pedrosoi, F. nubica [10], and C. carrionii [13] and associated CBM species such as Exophiala [11,12] and Cyphellophora [43]. Several studies have reported the application of the RCA padlock probe to detect species-specific fungal diseases with great public impact, e.g., in opportunistic infections caused by species of Candida [16], Aspergillus [16], and Cryptococcus [7,41]; agents associated with systemic infections such as Histoplasma [18], Fusarium [42] and Talaromyces marneffei [15]; and dermatophytoses caused by species of the genus Trichophyton [17].…”
Section: Discussionmentioning
confidence: 99%
“…73 PLP-RCA targeting the internal transcribed spacer rDNA of Histoplasma capsulatum, causing a systemic fungal disease called histoplasmosis, enabled the rapid and specific detection of the fungus in clinical samples. 74 Recently, PLP-RCA was used as an environmental screening tool for the detection of Fonsecaea agents causing chromoblastomycosis, a chronic cutaneous/subcutaneous mycosis with muriform cells in host tissue. 75 Such studies provide a promising scope toward accurate and timely detection of opportunistic infections including Candida, Rhizopus, and Mucor (causing mucormycosis, the "black fungus" disease manifested as an aftermath incidence in the current pandemic), that infect and invade human tissues in patients with weakened immunity (as in the case of COVID-19, HIV/AIDS, other viral diseases and cancers, for example).…”
Section: Diagnosis Of Fungal Infectionsmentioning
confidence: 99%